The Effect of Transformational Leadership Style, Work Motivation, and Work Discipline on Employee Performance - Arbaum Muawanah; Almira Santi Samasta (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
The purpose of this study is to evaluate how transformational leadership style, work motivation, and work discipline affect employee performance at the Alpha Indonesia Foundation in Central Java. The social background of the foundation, which includes various issues related to human resources and workplace dynamics, highlights the importance of this study. Using a census strategy, all 49 employees participated as respondents in this survey-based quantitative approach. A closed-ended questionnaire based on a Likert scale that had undergone validity and reliability testing to ensure measurement accuracy was used to collect data. The partial and simultaneous effects of these factors were evaluated using multiple linear regression analysis. Regardless of worker performance. The results of the study show that work motivation increases productivity, work discipline encourages regularity and consistency in job performance, and transformational leadership significantly improves employee morale. Overall, it has been proven that these three factors have a significant impact on the performance of agency employees. These results highlight the importance of intrinsic motivation, work discipline, and inspirational leadership as critical components in maximizing employee performance, especially in non-profit organizations involved in social and educational development.